Potential Antidiabetic and Anticancer Agents from the Inner bark Extractives of Mount Salak Forest Woods - Rita K Sari; Wasrin Syafii; Nur Azizah; Juliasman Juliasman; Muhammad Fadli; Minarti Minarti (Masyarakat Peneliti Kayu Indonesia, 2014)
The aim of this research was to determine the extract contents, antidiabetic and anticancer activities of the acetone extracts of the inner barks of beunying (Ficus fistulosa)/BE, hamerang (F. foxicaria)/HE, kilemo (Litsea cubeba)/KLE, kiseueur (Antidesma tetandrum)/KSE, kopo (Eugenia cymosa)/KOE, and pasang butarua (Quercus induta)/PBE from Mount Salak Forest. The phytochemical profile of the best extract as antidiabetic and anticancer agents was also determined. The investigation of antidiabetic and anticacer activities of this extracts was carried out through invitro inhibitory α-glucosidase test and toxicity test to Artemia salina. The content of acetone extract of the KSE, KOE, and BE contents were in the range of 4.3-7.8% (high), however that of the KLE, HE, and PBE contents were in the range of 3.0-3.9% (moderate). The acetone extract of the KSE was very active as α-glucosidase inhibitor (IC50 5.9 mg ml-1), the KLE, PBE, and BE were rated active with IC50 value 11.2, 17.2, and 43.2 mg ml-1 respectively, while the HE and KOE were inactive (IC50 > 100 mg ml-1). The acetone extract of the KSE was very toxic to A.salina (LC50 19.7 mg ml-1), these of the HE, KOE, and BE were toxic with LC50 value 79.5, 94.5, and 115.9 μg ml-1 respectively, while these of the KLE and PSE were inactive (LC50 > 250 mg ml-1). The most potential antidiabetic and anticancer agents was the acetone extract of KSE. The acetone extract of the KSE was detected with strong intensity containing alkaloids, flavonoids, and tannins.Keyword: anticancer, antidiabetic, α-glucosidase, innerbark extractives, Mount Salak Forest